A decision support framework for fatigue assessment of steel bridges. (September 2018) - Leander, John; Honfi, Dániel; Larsson Ivanov, Oskar; Björnsson, Ívar
Abstract: Many bridges are approaching or have already passed their expected service life. For steel bridges, fatigue is often the decisive degradation phenomenon that theoretically puts restrictions on a continued use. At the same time, fatigue is also afflicted with large uncertainties on the resistance side as well as on the action effect side. An accurate assessment of the service life will require measures outside the governing regulations but understanding what steps to take and how to consider the outcome for decisions on interventions can be a difficult task for a non-expert. This paper presents possible assessment actions and a decision support framework for rational decisions on interventions to extend the theoretical service life of existing bridges. A case study of a critical railway bridge is incorporated to demonstrate the framework. The aim is to provide a tool for bridge managers on how to evaluate and procure different assessment actions. Highlights: A Bayesian decision framework for fatigue assessment of steel bridges is presented. The framework aims at facilitating the procurement of enhanced assessments actions. The overall aim is to provide an extended theoretical service life of existing bridges. A case study is included to demonstrate the usefulness of the frame- work.